In silico Design and Synthesis of Tetrahydropyrimidinones and Tetrahydropyrimidinethiones as Potential Thymidylate Kinase Inhibitors Exerting Anti-TB Activity Against Mycobacterium tuberculosis - Venugopala KN; Tratrat C; Pillay M; Chandrashekharappa S; Al-Attraqchi OHA; Aldhubiab BE; Attimarad M; Alwassil OI; Nair AB; Sreeharsha N; Venugopala R; Morsy MA; et al. (Dove Medical Press, 2020)
Katharigatta N Venugopala, 1, 2 Christophe Tratrat, 1 Melendhran Pillay, 3 Sandeep Chandrashekharappa, 4 Omar Husham Ahmed Al-Attraqchi, 5 Bandar E Aldhubiab, 1 Mahesh Attimarad, 1 Osama I Alwassil, 6 Anroop B Nair, 1 Nagaraja Sreeharsha, 1 Rashmi Venugopala, 7 Mohamed A Morsy, 1, 8 Michelyne Haroun, 1 Hezekiel M Kumalo, 9 Bharti Odhav, 2 Koleka Mlisana 3 1Department of Pharmaceutical Sciences, College of Clinical Pharmacy, King Faisal University, Al-Ahsa 31982, Kingdom of Saudi Arabia; 2Department of Biotechnology and Food Technology, Durban University of Technology, Durban 4001, South Africa; 3Department of Microbiology, National Health Laboratory Services, KZN Academic Complex, Inkosi Albert Luthuli Central Hospital, Durban 4001, South Africa; 4Institute for Stem Cell Biology and Regenerative Medicine, NCBS, TIFR, Bangalore 560 065, India; 5Department of Pharmaceutical Sciences, Faculty of Pharmacy, Philadelphia University, Amman 19392, Jordan; 6Department of Pharmaceutical Sciences, College of Pharmacy, King Saud Bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 7Department of Public Health Medicine, University of KwaZulu-Natal, Howard College Campus, Durban 4001, South Africa; 8Department of Pharmacology, Faculty of Medicine, Minia University, El-Minia 61511, Egypt; 9Department of Medical Biochemistry, School of Laboratory Medicine and Medical Sciences, University of KwaZulu-Natal, Medical School, Durban 4001, South AfricaCorrespondence: Katharigatta N VenugopalaDepartment of Pharmaceutical Sciences, College of Clinical Pharmacy, King Faisal University, P.o. Box-400, Al-Ahsa 31982, Kingdom of Saudi ArabiaTel +96613 589 8842Email kvenugopala@kfu.edu.saSandeep ChandrashekharappaInstitute for Stem Cell Biology and Regenerative Medicine, National Center for Biological Sciences, Tata Institute of Fundamental Research, GKVK, Bellary Road, Bangalore 560 065, IndiaTel +9194486 39413Email sandeepc@instem.res.inBackground and Purpose: Tuberculosis has been reported to be the worldwide leading cause of death resulting from a sole infectious agent. The emergence of multidrug-resistant tuberculosis and extensively drug-resistant tuberculosis has made the battle against the infection more difficult since most currently available therapeutic options are ineffective against these resistant strains. Therefore, novel molecules need to be developed to effectively treat tuberculosis disease. Preliminary docking studies revealed that tetrahydropyrimidinone derivatives have favorable interactions with the thymidylate kinase receptor. In the present investigation, we report the synthesis and the mycobacterial activity of several pyrimidinones and pyrimidinethiones as potential thymidylate kinase inhibitors.Methods: The title compounds ( 1a–d) and ( 2a–b) were synthesized by a one-pot three-component Biginelli reaction. They were subsequently characterized and used for whole-cell anti-TB screening against H37Rv and multidrug-resistant (MDR) strains of Mycobacterium tuberculosis (MTB) by the resazurin microplate assay (REMA) plate method. Molecular modeling was conducted using the Accelry’s Discovery Studio 4.0 client program to explain the observed bioactivity of the compounds. The pharmacokinetic properties of the synthesized compounds were predicted and analyzed.Results: Of the compounds tested for anti-TB activity, pyrimidinone 1a and pyrimidinethione 2a displayed moderate activity against susceptible MTB H37Rv strains at 16 and 32 μg/mL, respectively. Only compound 2a was observed to exert modest activity at 128 μg/mL against MTB strains with cross-resistance to rifampicin and isoniazid. The presence of the trifluoromethyl group was essential to retain the inhibitory activity of compounds 1a and 2a. Molecular modeling studies of these compounds against thymidylate kinase targets demonstrated a positive correlation between the bioactivity and structure of the compounds. The in-silico ADME (absorption, distribution, metabolism, and excretion) prediction indicated favorable pharmacokinetic and drug-like properties for most compounds.Conclusion: Pyrimidinone 1a and pyrimidinethione 2a were identified as the leading compounds and can serve as a starting point to develop novel anti-TB therapeutic agents.Keywords: thymidylate kinase inhibitors, tetrahydropyrimidinones, tetrahydropyrimidinethiones, multidrug resistance, Mycobacterium tuberculosis, molecular modeling